Mechanical Strength of Organic Soil Treated by Fiber Incorporated Microbial Cementation. - Gowthaman, S.; Nayanthara, P.G.N.; Nakashima, H.; Kawasaki, S.; Sato, A. (Southeast University, Nanjing, China., 2020)
Peat lands are formed by the gradual accumulation of the remains of dead plant vegetation under waterlogged conditions. Facilitating structures and access paths on a peat deposit pose an enormous challenge owing to the low bearing strength and excessive settlement. Within a past decade, use of microbial induced carbonate precipitation (MICP) has become very popular ground improvement technique due to its viability and cost effectiveness over the conventional treatment methods. This research work aims to investigate the feasibility of fiber incorporated microbial cementation to improve the peat soil, henceforth to provide the access path on peat deposit of Hokkaido, Japan. The urease positive bacteria isolated from the native peat soil was characterized and used for the microbial treatment. The bamboo fibers that are rich in cellulose and lignin i.e. more durable, were incorporated. The soil was treated by mixing the fibers and MICP sources at different weight ratios; all the chemical resources except the bacteria culture were introduced in dry state. The improvement of peat soil was assessed by measuring the early and late undrained shear strength by using fall cone test after 48 hours and 7 days respectively. The results suggest that the fiber incorporated microbial cementation increased the shear strength significantly by around 45 times higher, whereas the treatment without fiber could increase the strength only by around 5 times compared to that of untreated. The bamboo fibers could play two prime roles: decreased the moisture content and increase the denseness of peat soil, hence supplied more resistance to shear. Moreover, carbonate precipitated on fibers increased the surface roughness and formed the bonds between the adjacent fibers, leading to significant improvement in stiffness and shear strength. Further studies are recommended to investigate the effect on improving the compressibility and settlement of peat.
Keywords: MICP; Peat soil; Bamboo fiber; Fall cone test; Undrained shear strength; Native bacteria